Digital-Based Public Communication of Public Relations of the Sleman Regency Government During the COVID-19 Pandemic - Nurjanah, Adhianty (Universitas Muhammadiyah Ponorogo, 2023)
Public communication is important in handling Covid-19, both for prevention and as persuasion to apply the Covid-19 vaccination. As was done by the Public Relations of the Sleman Regency Government as the spokesperson for the Covid-19 Task Force which has proven to make Sleman the province with the highest handling of Covid-19 vaccinations. Public Relations of the Sleman Regency Government actively conveys public communication regarding the handling and prevention of the Covid-19 pandemic with a digital approach. This shows the importance of digital-based public communication during a pandemic. This study aims to determine the digital-based Sleman Regency Government Public Relations communication model in handling Covid-19. This research uses a descriptive qualitative approach with a case study method. The use of case studies considering that this research is very specific in discussing how the communication model carried out by the Public Relations of the Sleman Regency Government in communicating messages for persuasiveness to vaccination in Kab. Sleman is the highest. Data collection was carried out through in-depth interviews and FGDs with Public Relations of the Sleman Regency Government, Regional Apparatus Organizations (OPD), and the people of Sleman. The results of the study revealed that the Public Relations of the Sleman Regency Government was a spokesperson who was trusted to convey information related to the Covid-19 pandemic. The disaster communication model carried out by the Public Relations of the Sleman Regency Government, namely adapting the information determined from the Central Government then packaging it back in local languages and selecting trusted figures then utilizing digital media such as the Website, Facebook and Twitter @KabarSleman and on Instagram @HumasSleman to convey messages. In addition, Public Relations still uses conventional media such as newspapers, outdoor media and digital outdoor media such as LED. This research has a novelty value that the government must have one voice in public communication even though it uses various channels. The information provided to the public is designed to follow the central government's appeal to have the same news value so as not to cause public confusion.